A Historical Survey of the Plant-Based Industry of the Nembe Se: A Springboard for Sustainable Development in Nigeria - David, Emi Numo (dialektika kontemporer, 2025)
Plant-based industries, also referred to as agro-based industries, encompass all industries that maintain a direct or indirect connection with agriculture. Beyond the primary production sector, weaving and textile manufacturing constitute significant components of this industry. This study intends to document the history of the Plant-based industry of the Nembe Se from the earliest times to the present day. To address the research questions, the study employed a combination of oral sources, secondary materials, and observational methods of data collection to highlight and explore the various aspects of these industrial sectors. The results of this study reveal the profound environmental influences on the socioeconomic development, activities, systems, and potential of the indigenous Plant-based industry of the Nembe people. The findings also illuminate the mutations and continuities that have resulted from developmental efforts and modernism. The study examines the factors that have militated against the activities of the Nembe indigenous Plant-based industries over time. The implications of this study could be used to promote further investigation into the development of various indigenous industries across Nigeria. Among other contributions, the study presents recommendations for both the indigenes and the government to improve the Plant-based industrial sectors for sustainable development.